Practicality of STEAM–SDGs-Based IPAS Learning for Vocational Students in the Green Economy Era - Siti Patonah; Idha Budiati; Muhammad Syaipul Hayat (CV FOUNDAE, 2025)
The transformation of vocational education in the green economy era requires learning models that extend beyond technical skill mastery to foster creativity and environmental awareness. This study aimed to develop and evaluate the practicality of a STEAM–SDGs-based IPAS learning model through a renewable energy–based Smart House project for vocational students. Thirty tenth-grade software engineering students and one teacher participated. Using the ADDIE framework, data were collected through dichotomous practicality questionnaires, classroom observations, and semi-structured interviews and analyzed descriptively. Findings indicate that the instructional materials—including modules, student worksheets, and assessment instruments—are highly practical, supporting structured lesson planning, collaborative project management, and coherent facilitation of hands-on activities. The model enhanced students’ creative thinking, particularly imagination and originality, and strengthened environmental literacy, including ecological knowledge and energy awareness, though emotional reflection and pro-environmental behaviours were less pronounced. Overall, the model is practical, contextually relevant, and adaptable, offering a viable framework for fostering twenty-first-century competencies and preparing students for the green economy, while reinforcing the integration of STEAM pedagogy with SDG 7 in vocational education.